Factors influencing farming households' climate change adaptation strategies in Central Vietnam. - Bui Huy Nhuong; Dinh Duc Truong; Le Huy Huan; Bui Thi Hoang Lan; Nguyen Dieu Hang; Duong Duc Tam (PLoS ONE, 2025)
This study investigates the determinants of household-level adaptation strategies to climate variability and saltwater intrusion in the coastal regions of Central Vietnam. Using a Multinomial Logistic Regression (MNL) model, the analysis is based on a cross-sectional survey of 356 farming households, focusing on four primary adaptation measures: vegetable production, shrimp farming, adoption of salt-tolerant rice varieties, and the lotus-fish farming model. The results reveal that socio-economic, demographic, environmental, and institutional factors significantly influence the adoption of specific adaptation strategies. Key determinants include gender, education, age, farming experience, household income, land characteristics, access to information, credit services, membership in civic organizations, and participation in training programs. Male-headed households and those with greater access to climate information and social networks were more likely to adopt diverse and complex adaptation strategies. In contrast, households with limited land resources, lower incomes, or lacking institutional support were less adaptive. The findings highlight the heterogeneity of adaptive behaviors and the need for tailored interventions. From a policy perspective, enhancing institutional capacity-especially through targeted training, increased access to subsidized credit, and support for community-based organizations-can significantly strengthen farmers' adaptive capacities. Moreover, the study contributes to filling key research gaps in the Southeast Asian context by integrating socio-economic and environmental variables into a unified analytical framework. These insights are critical for designing inclusive and effective climate adaptation policies aimed at safeguarding rural livelihoods and promoting sustainable agricultural development in climate-vulnerable regions.